2015
DOI: 10.2298/abs141010017d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen on the distribution of biomass and element composition of the root system of miscanthus × giganteus

Abstract: Perennial bioenergy grass crops, despite a relatively similar production of aboveground biomass, show significant differences in the overall root biomass. Rhizomes play a key role in economizing nutrients in miscanthus. The aim of this research was to establish the effect of N (nitrogen) on the distribution of biomass and concentration of major macro- and micronutrients in the miscanthus root system, using simple experiment in pots. After two years of growth, the rhizomes and roots were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…There were also statistically significant variations between individual treatments (Table 2, Figure 3a). The impact of meteorological conditions and nitrogen fertilizers on the yield of stalks was significant, which was also found in the research by Gonzalez-Dugo et al (2010); Dželetović et al (2013); Dželetović and Glamočlija (2015); Glamočlija et al (2018) and Đurić et al (2019).…”
Section: Number Of Stalks In Tiller Period Nostlsupporting
confidence: 68%
“…There were also statistically significant variations between individual treatments (Table 2, Figure 3a). The impact of meteorological conditions and nitrogen fertilizers on the yield of stalks was significant, which was also found in the research by Gonzalez-Dugo et al (2010); Dželetović et al (2013); Dželetović and Glamočlija (2015); Glamočlija et al (2018) and Đurić et al (2019).…”
Section: Number Of Stalks In Tiller Period Nostlsupporting
confidence: 68%
“…During the first season, miscanthus develops a loose root system, with the original rhizome in the center. In the second season, a dense system of lateral roots is formed together with a great number of new rhizomes (Dželetović and Glamočlija, 2015). Humentyk et al (2013) found that, in the first season when the mass of the planted rhizomes was 20-30 g, at the end of the vegetation season, the root system mass amounted to 471 g (the 18-fold increase), while with the rhizomes of 90-120 g, the total root system mass amounted to 664 g (the 6-fold increase).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the majority of other agricultural crops, miscanthus is a plant with an extensive root system, which remains dormant during winter, but it may respond quickly to increased plant requirement for assimilates at the start of growing season in the spring (Himken et al, 1997). Rhizome mass comprises approximately 2/3 of root biomass (Dželetović and Glamočlija, 2015). It has a shallow root system, with almost 90% of root biomass concentrated in the surface soil layer (0-35 cm) (Monti and Zatta, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus biomass is presently used in the combustion process [14] as an ideal fuel plant, providing annual easy cultivation, harvesting, and high yields of dry matter [9]. The examination of the biomass chemical composition is necessary to test the suitability for bioenergy conversion [15], which is indispensable for the production of derived fuels and chemical substances [16]. The determination of the nutrient composition in plants is crucial, not only in the combustion process but also for examining the nutrient uptake by crops [17].…”
Section: Introductionmentioning
confidence: 99%